Injectable cell transplantation system for cytokine-based cancer immunotherapy - Gerard Nathanael Adrianus. (2009)
Cancer is a major killing disease, causing 6.7 million deaths globally in 2002. Standard cancer treatments, such as chemotherapy and radiation, are either not effective or result in temporary tumour regression while causing excessive damage to normal tissues. Immunotherapy is a promising therapy that attempts to use components of the immune system to bolster host immune rejection against tumour tissues. Cytokines, the regulatory peptides that control modulation of cell proliferation, differentiation, and survival, have been widely studied for cancer immunotherapy. Systemic injection of most cytokines has only shown modest clinical benefits, while associated with significant side-effects akin to chronic inflammation. Local, targeted delivery of cytokines in tumour sites is beneficial to achieve high therapeutic dose within tumour while limiting systemic dose.